High-strength steel plates and automobile bodies
Patent Information
- Application Number
- JP2022045021
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-03-22
AI Technical Summary
【0013】 本発明の高強度鋼板は、遅れ破壊が効果的に抑制される優れた耐遅れ破壊性を有するとともに、優れた耐食性を有する。本発明の高強度鋼板は、自動車、建材用の強度部材に好適に用いられる。特に、自動車車体の中で、高強度が必要とされ、かつ、腐食環境が厳しいサイドシル、センターピラー下部、バンパー等の自動車車体の下部構造部材やロアアーム等の自動車車台(シャシー)構造部材に好適に用いることが出来る。
Smart Images

Figure 0007605164000003 
Figure 0007605164000004 
Figure 0007605164000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a high-strength steel plate having excellent delayed fracture resistance, and more particularly to a high-strength steel plate suitable for use mainly in strength members for automobiles and building materials, which has excellent delayed fracture resistance and corrosion resistance and a tensile strength of 1180 MPa or more. [Background technology]
[0002] Galvanized steel sheets have traditionally been widely used for automobiles. This is because the sacrificial corrosion protection effect of zinc significantly improves the corrosion resistance of steel sheets after painting. In recent years, efforts have been made to increase the strength of automotive steel sheets in order to reduce CO2 emissions and ensure safety.
[0003] However, it is known that increasing the strength of steel makes it more susceptible to a phenomenon known as delayed fracture. This delayed fracture becomes more likely as the strength of the steel increases, and is particularly noticeable in high-strength steel with a tensile strength of 1180 MPa or more. Delayed fracture is a phenomenon in which high-strength steel is subjected to static load stress (load stress less than the tensile strength) and, after a certain period of time, suddenly undergoes brittle fracture without any apparent plastic deformation.
[0004] It is known that delayed fracture occurs in steel sheets due to residual stresses generated when the steel sheet is pressed into a predetermined shape and hydrogen embrittlement of the steel at stress concentration points. The hydrogen that causes this hydrogen embrittlement is thought to be hydrogen that penetrates into the steel from the external environment and diffuses therein. A typical example is hydrogen that is generated during corrosion of the steel sheet and penetrates and diffuses into the steel. In general, galvanized steel sheets penetrate more hydrogen during corrosion than cold-rolled steel sheets, and are therefore exposed to a more severe environment for delayed fracture.
[0005] In particular, among automotive structural components, the lower structural components of the automobile body, such as the side sills (rockers), lower center pillars (B-pillars), and bumpers, as well as the chassis structural components, such as the lower arms, are subject to severe corrosive environments and are areas where measures to prevent delayed fracture are particularly required.
[0006] In order to prevent such delayed fracture in high-strength steel sheets, for example, Patent Document 1 studies reducing the delayed fracture susceptibility by adjusting the structure and components of the steel sheet. Also, Patent Document 2 studies high-strength hot-dip galvanized steel sheets that prevent delayed fracture. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Laid-Open No. 2004-231992 [Patent Document 2] Japanese Patent Application Publication No. 6-145893 Summary of the Invention [Problem to be solved by the invention]
[0008] However, the technology disclosed in Patent Document 1 does not change the amount of hydrogen that penetrates into the steel sheet from the external environment, so although it can delay the occurrence of delayed fracture, it cannot prevent delayed fracture itself. Furthermore, even when the steel composition and microstructure were adjusted based on the technology disclosed in Patent Document 2, sufficient delayed fracture resistance could not be obtained.
[0009] Therefore, high strength steel sheets that are excellent in both corrosion resistance and delayed fracture resistance have not yet been put to practical use.
[0010] An object of the present invention is to solve the above-mentioned problems of the prior art and to provide a high-strength steel sheet excellent in delayed fracture resistance and corrosion resistance, which is suitable mainly for strength members of automobiles. [Means for solving the problem]
[0011] In order to solve the above problems, the present inventors have conducted extensive research and studies into means for preventing delayed fracture by suppressing hydrogen penetration into the steel sheet. As a result, they have found that by coating the surface of a substrate steel sheet with a Zn-Co alloy layer having a specific coating amount and a specific Co concentration, hydrogen penetration into the steel sheet can be significantly suppressed, preventing delayed fracture of the steel sheet, and also achieving excellent corrosion resistance.
[0012] The present invention was made based on these findings and has the following gist. [1] A substrate steel sheet having a tensile strength of 1180 MPa or more and a Zn-Co alloy layer coated on the surface of the substrate steel sheet, The Zn-Co alloy layer has a coating amount of 0.10 g / m 2 That's all, and a Co concentration in the Zn-Co alloy layer is 5% by mass or more and less than 60% by mass. [2] The coating amount of the Zn-Co alloy layer is 20 g / m 2 The high-strength steel plate according to [1], characterized in that: [3] The high-strength steel plate according to [1] or [2], characterized in that the Co concentration is 10 mass % or more and less than 30 mass %. [4] The coating amount of the Zn-Co alloy layer is 90 g / m 2 The high-strength steel plate according to any one of [1] to [3], characterized in that it is less than [5] The high-strength steel sheet according to any one of [1] to [4], characterized in that the base steel sheet has a chemical composition containing, in mass%, C: 0.03% or more and 0.45% or less, Si: 0.01% or more and 3.00% or less, Mn: 0.5% or more and 3.5% or less, P: 0.050% or less, S: 0.0050% or less, Al: 0.001% or more and 1.500% or less, and N: 0.0100% or less, with the balance being Fe and unavoidable impurities. [6] The high-strength steel sheet according to [5], characterized in that the base steel sheet further contains, in mass%, one or more elements selected from Cu: 1.000% or less, B: 0.0050% or less, Nb: 0.100% or less, Ti: 0.200% or less, V: 0.500% or less, Mo: 1.000% or less, Cr: 1.000% or less, Ni: 1.00% or less, W: 0.200% or less, Zr: 0.200% or less, Hf: 0.200% or less, Co: 0.500% or less, Ca: 0.0050% or less, Mg: 0.0100% or less, Sn: 0.200% or less, Sb: 0.200% or less, and REM: 0.005% or less. [7] An automobile body or automobile suspension part using the high-strength steel sheet according to any one of [1] to [6]. [8] An automobile body using the high-strength steel sheet according to any one of [1] to [6] in one or more locations among a side sill, a lower part of a center pillar, and a bumper. [9] An automobile chassis using the high-strength steel plate according to any one of [1] to [6] in a lower arm portion. [Effects of the Invention]
[0013] The high-strength steel sheet of the present invention has excellent delayed fracture resistance, in which delayed fracture is effectively suppressed, and also has excellent corrosion resistance. The high-strength steel sheet of the present invention is suitable for use in strength members for automobiles and building materials. In particular, it can be suitable for use in automobile body lower structural members such as side sills, lower center pillars, and bumpers, which require high strength and are subject to severe corrosive environments, and automobile chassis structural members such as lower arms. [Brief explanation of the drawings]
[0014] [Figure 1] 1 is a diagram schematically showing a test piece for evaluating delayed fracture used in Examples. [Figure 2] FIG. 2 is an explanatory diagram showing the steps of a combined cycle corrosion test carried out in the examples. DETAILED DESCRIPTION OF THE INVENTION
[0015] The high-strength steel sheet of the present invention has a substrate steel sheet having a tensile strength of 1180 MPa or more and a Zn-Co alloy layer coated on the surface of the substrate steel sheet, and the Zn-Co alloy layer has a coating amount of 0.10 g / m 2 The Zn-Co alloy layer has a Co concentration of 5% by mass or more and less than 60% by mass, and is excellent in delayed fracture resistance and corrosion resistance.
[0016] The steel sheet (base steel sheet) that serves as the substrate of the high-strength steel sheet of the present invention is a steel sheet having a tensile strength of 1180 MPa or more, preferably 1320 MPa or more. Delayed fracture occurs when hydrogen penetrates into steel and diffuses or concentrates in stress-concentrated areas, causing embrittlement, and is therefore dependent on the strength of the steel. That is, delayed fracture is essentially less likely to occur in steel sheets with low tensile strength. Therefore, although the effects of the present invention can be obtained with steel sheets with low tensile strength, they are most pronounced in steel sheets with a tensile strength of 1180 MPa or more, and even more pronounced in steel sheets with a tensile strength of 1320 MPa or more.
[0017] Lower structural components of automobile bodies, such as side sills, lower center pillars, and bumpers, as well as chassis structural components, such as lower arms, are required to have a tensile strength of 1180 MPa or more in order to ensure high crashworthiness and a lightweight structure. Furthermore, the corrosive environment of these lower structural components is prone to corrosion due to the accumulation of mud and saltwater during driving, so they require superior corrosion resistance compared to the upper structure of the automobile body.
[0018] The tensile strength can be measured in accordance with JIS Z 2241 (2011).
[0019] The chemical composition and steel structure of the base steel sheet are not particularly limited. Furthermore, the rolling method is also not particularly limited, and either a hot-rolled steel sheet or a cold-rolled steel sheet may be used as the base steel sheet. Among these, it is preferable to use a cold-rolled steel sheet, considering that steel sheets are used in the automotive and building material fields, particularly in the automotive field. That is, the base steel sheet of the present invention is preferably a high-strength cold-rolled steel sheet having a tensile strength of 1180 MPa or more, and more preferably a high-strength cold-rolled steel sheet having a tensile strength of 1320 MPa or more.
[0020] The base steel sheet preferably used in the present invention may have any chemical composition and steel structure as long as it has the desired tensile strength. In order to improve various properties such as mechanical properties, the following structural or chemical modifications may be used alone or in combination: solid solution strengthening by the addition of interstitial solid solution elements such as C and N or substitutional solid solution elements such as Si, Mn, P and Cr; precipitation strengthening by carbonitrides such as Ti, Nb, V and Al; addition of strengthening elements such as W, Zr, Hf, Co, B, Cu and rare earth elements; strengthening by recovery annealing at a temperature at which recrystallization does not occur or partial recrystallization strengthening by leaving unrecrystallized regions without complete recrystallization; strengthening by transformation structure such as formation of a single phase of bainite or martensite or a composite structure of ferrite and these transformed structures; grain refinement strengthening expressed by the Hall-Petch equation σ=σ+kd (where σ is stress, σ and k are material constants) where d is the ferrite grain size; and working strengthening by rolling or the like.
[0021] The chemical composition of such a base steel sheet may, for example, contain, in mass%, C: 0.03% or more and 0.45% or less, Si: 0.01% or more and 3.00% or less, Mn: 0.5% or more and 3.5% or less, P: 0.050% or less, S: 0.0050% or less, Al: 0.001% or more and 1.500% or less, N: 0.0100% or less, and further Cu: 1.000% or less, B: 0.0050% or less, Nb: 0.100% or less, Ti: 0.200% or less, and V: 0.500% or less. The composition may contain one or more elements selected from the group consisting of Mo: 1.000% or less, Cr: 1.000% or less, Ni: 1.00% or less, W: 0.200% or less, Zr: 0.200% or less, Hf: 0.200% or less, Co: 0.500% or less, Ca: 0.0050% or less, Mg: 0.0100% or less, Sn: 0.200% or less, Sb: 0.200% or less, and REM: 0.005% or less, with the balance being Fe and unavoidable impurities. Note that due to production technology constraints, the content of P, S, and N may exceed 0%.
[0022] The chemical composition of the steel sheet of the present invention will be described below. Note that % indications regarding the components mean mass % unless otherwise specified.
[0023] C: 0.03% or more and 0.45% or less C has the effect of increasing the strength of steel sheets. To obtain this effect, a C content of 0.03% or more is preferable. On the other hand, if the C content exceeds 0.45%, the weldability, which is necessary for use as a material for automobiles and home appliances, deteriorates. Therefore, the C content may be set to 0.03% or more and 0.45% or less.
[0024] Si: 0.01% or more and 3.00% or less Silicon is an effective element for strengthening steel and improving ductility, and to obtain this effect, a silicon content of 0.01% or more is preferred. On the other hand, if the silicon content exceeds 3.00%, silicon forms oxides on the surface, deteriorating the coating appearance. Therefore, the silicon content may be set to 0.01% or more and 3.00% or less. A more preferred range is 0.01% or more and 2.00% or less.
[0025] Mn: 0.5% or more and 3.5% or less Mn is a useful element for improving hardenability and increasing the strength of steel sheets. This effect cannot be obtained if the Mn content is less than 0.5%. On the other hand, if the Mn content exceeds 3.5%, Mn segregation occurs, resulting in a decrease in workability. Therefore, the Mn content may be set to 0.5% or more and 3.5% or less. From the viewpoint of improving workability, it is preferable that Mn be set to 3.0% or less.
[0026] P:0.050% or less P is one of the elements that is inevitably contained, and since reducing the P content to less than 0.005% is likely to increase costs, it is desirable for the P content to be 0.005% or more. On the other hand, if the P content exceeds 0.050%, P segregation to austenite grain boundaries during casting causes grain boundary embrittlement, which deteriorates local ductility and therefore degrades the delayed fracture resistance of the steel sheet after forming. Therefore, it is preferable to reduce the P content as much as possible, and the P content may be 0.050% or less. Preferably, the P content is 0.020% or less.
[0027] S: 0.0050% or less S is an element that is inevitably contained in the steelmaking process. However, if it is contained in a large amount, it deteriorates weldability. Therefore, the S content may be set to 0.0050% or less. From the viewpoint of improving delayed fracture resistance, S is preferably set to 0.0020% or less. Since there is a concern that increasing costs will occur if S is set to 0.0001% or less, it is preferable that S is set to 0.0002% or more.
[0028] Al: 0.001% or more and 1.500% or less Al is added to deoxidize molten steel, but if its content is less than 0.001%, this purpose will not be achieved. On the other hand, if the Al content exceeds 1.500%, Al and N will combine to form nitrides. These nitrides precipitate on austenite grain boundaries during casting, causing grain boundary embrittlement and deteriorating delayed fracture resistance. Therefore, the Al content should be between 0.001% and 1.500%.
[0029] N: 0.0100% or less N combines with Al to form nitrides. Nitrides precipitate on austenite grain boundaries during casting, causing embrittlement and degrading delayed fracture resistance. Therefore, the N content is set to 0.0100% or less. From the above perspective, N is preferably set to 0.0050% or less. Reducing N to 0.0001% or less would increase costs, so it is preferable that it be 0.0005% or more.
[0030] Cu:1.000% or less Cu has the effect of suppressing dissolution of steel sheet in a corrosive environment and reducing the amount of hydrogen that penetrates into the steel. On the other hand, a Cu content of more than 1.000% leads to increased costs. Therefore, the Cu content may be set to 1.000% or less. To obtain the above effects, the Cu content is preferably set to 0.005% or more.
[0031] B: 0.0050% or less The addition of B has the effect of promoting hardening. On the other hand, if the B content exceeds 0.0050%, the number of inclusions increases and the delayed fracture resistance deteriorates. Therefore, the B content may be set to 0.0050% or less.
[0032] Nb: 0.100% or less At 0.005% or more, Nb has the effect of improving strength. On the other hand, if the Nb content exceeds 0.100%, the amount of inclusions increases, deteriorating delayed fracture resistance and increasing costs. Therefore, when Nb is contained, the Nb content may be 100% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, it is more preferable that the Nb content be 0.050% or less.
[0033] Ti:0.200% or less A Ti content of 0.005% or more can improve strength. On the other hand, a Ti content of more than 0.200% increases inclusions, deteriorating delayed fracture resistance. Therefore, when Ti is contained, the Ti content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, a Ti content of 0.080% or less is even more preferable.
[0034] V:0.500% or less Fine carbides formed by the combination of V and C are effective in improving delayed fracture resistance by strengthening the precipitation of the steel sheet and acting as hydrogen trapping sites, so V may be added as needed. If the V content exceeds 0.500%, excessive carbides may precipitate, potentially deteriorating the strength-ductility balance. For this reason, the V content is preferably 0.500% or less, more preferably 0.100% or less, and even more preferably 0.050% or less. In the present invention, a V content of 0.005% or more is preferred to achieve the above effects.
[0035] Mo: 1.000% or less Mo has the effect of improving strength when it is 0.005% or more. On the other hand, if the Mo content exceeds 1.000%, costs increase. Therefore, when Mo is contained, the Mo content may be 1.000% or less, and preferably 0.005% or more.
[0036] Cr:1.000% or less A Cr content of 0.005% or more provides a hardenability effect. On the other hand, if the Cr content exceeds 1.000%, Cr concentrates on the surface, deteriorating weldability. Therefore, if Cr is contained, the Cr content may be 1.000% or less, and preferably 0.005% or more.
[0037] Ni: 1.00% or less Ni content of 0.005% or more has the effect of promoting the formation of residual γ phase. On the other hand, Ni content exceeding 1.00% leads to increased costs. Therefore, when Ni is contained, the Ni content may be 1.00% or less, and preferably 0.005% or more.
[0038] W: 0.200% or less A W content of 0.005% or more can improve strength. On the other hand, a W content of more than 0.200% increases the number of inclusions, deteriorating delayed fracture resistance and increasing costs. Therefore, if W is contained, the W content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, it is more preferable that the W content be 0.030% or less.
[0039] Zr: 0.200% or less A Zr content of 0.005% or more can improve strength. On the other hand, a Zr content of more than 0.200% increases inclusions, degrading delayed fracture resistance and increasing costs. Therefore, if Zr is contained, the Zr content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, a Zr content of 0.030% or less is even more preferable.
[0040] Hf: 0.200% or less Hf at 0.005% or more has the effect of improving strength. On the other hand, if the Hf content exceeds 0.200%, the amount of inclusions increases, deteriorating delayed fracture resistance and increasing costs. Therefore, if Hf is contained, the Hf content may be 0.200% or less, and preferably 0.005% or more. From the viewpoint of reducing inclusions, it is more preferable that the Hf content be 0.030% or less.
[0041] Co:0.500% or less Co content of 0.005% or more has the effect of improving ductility. On the other hand, a Co content exceeding 0.500% leads to a significant increase in costs. Therefore, when Co is contained, the Co content may be 0.500% or less, and preferably 0.005% or more.
[0042] Ca: 0.0050% or less At 0.0002% or more, Ca has the effect of spheroidizing inclusions and improving delayed fracture resistance. On the other hand, at a Ca content of more than 0.0050%, the number of inclusions increases, deteriorating delayed fracture resistance and increasing costs. Therefore, when Ca is contained, the Ca content may be 0.0050% or less, and preferably 0.0002% or more.
[0043] Mg: 0.0100% or less At 0.0002% or more, Mg has the effect of spheroidizing inclusions and improving delayed fracture resistance. On the other hand, at a Mg content of more than 0.0100%, the number of inclusions increases, deteriorating delayed fracture resistance and increasing costs. Therefore, when Mg is contained, the Mg content may be 0.0100% or less, and preferably 0.0002% or more.
[0044] Sn: 0.200% or less At 0.002% or more, Sn has the effect of suppressing decarburization of the surface layer and improving fatigue resistance. On the other hand, at an Sn content of more than 0.200%, it embrittles the grain boundaries, degrading delayed fracture resistance and increasing costs. Therefore, if Sn is contained, the Sn content may be 0.200% or less, and preferably 0.002% or more.
[0045] Sb: 0.200% or less At 0.002% or more, Sb has the effect of suppressing decarburization of the surface layer and improving fatigue resistance. On the other hand, an Sb content of more than 0.200% embrittles the grain boundaries, degrading delayed fracture resistance and increasing costs. Therefore, if Sb is contained, the Sb content may be 0.200% or less, and preferably 0.002% or more.
[0046] REM: 0.005% or less At 0.0002% or more, rare-earth metal (REM) has the effect of spheroidizing inclusions and improving delayed fracture resistance. On the other hand, at an REM content of more than 0.005%, the number of inclusions increases, deteriorating delayed fracture resistance and increasing costs. Therefore, if REM is contained, the REM content should be 0.005% or less, and preferably 0.0002% or more.
[0047] The balance is Fe and unavoidable impurities.
[0048] In addition, when the content of B, Cu, Nb, Ti, Mo, Cr, Ni, W, Zr, Hf, Co, Ca, Mg, Sn, Sb, and REM, which are described as the preferable ranges of the above components, is less than the lower limit, the component is considered to be contained as an unavoidable impurity.
[0049] In the present invention, the thickness of the base steel sheet that serves as the substrate is not particularly limited, but is preferably 0.8 to 6.0 mm, more preferably 1.2 to 4.0 mm.
[0050] The high-strength steel sheet of the present invention is a steel sheet (base steel sheet) having a surface coated with a specific Zn-Co alloy layer, i.e., a coating amount of 0.10 g / m 2 The material is coated with a Zn-Co alloy layer having a Co concentration of 5 mass % or more and less than 60 mass %.
[0051] Based on the results of research and investigations conducted by the present inventors, we have concluded that the generation of a large amount of hydrogen on the substrate steel due to the sacrificial corrosion protection effect of the Zn coating during the corrosion process in wet conditions is a major factor in the delayed fracture of the steel sheet. We have also discovered that, in order to suppress hydrogen penetration into the steel sheet, it is particularly important to suppress hydrogen penetration into the steel sheet during the corrosion process. We have concluded that in the case of Zn-Co coating, the Co forms corrosion products with a high corrosion-inhibiting effect during the corrosion process, which can suppress hydrogen penetration into the steel sheet.
[0052] From the above estimated mechanism, it is considered that the coating amount of the Zn-Co alloy layer on the steel sheet surface needs to be 0.10 g / m in order to form corrosion products that are effective in suppressing hydrogen penetration. 2 It was found that the Co concentration in the Zn-Co alloy layer must be 5 mass % or more and less than 60 mass %. In addition, when applied to members that are particularly susceptible to corrosion, the coating amount of the Zn-Co alloy layer must be 20 g / m 2 It is preferable that the above is set.
[0053] The coating weight of the Zn-Co alloy layer is 0.10 g / m 2 If the coating weight of the Zn-Co alloy layer is less than 0.10 g / m, it is not possible to achieve both a sufficient effect of suppressing hydrogen penetration and an effect of improving corrosion resistance. 2When the coating weight of the Zn-Co alloy layer is too low compared to 90 g / m, the amount of hydrogen penetration can be reduced, but the desired corrosion resistance cannot be obtained. 2 Therefore, it is preferable that the coating amount of the Zn-Co alloy layer is less than 0.10 g / m because a significant increase in manufacturing costs can be prevented. 2 More preferably, it is 20 g / m 2 More preferably, it is 40 g / m or more. 2 More than 60g / m 2 Less than 40g / m 2 More than 60g / m 2 If the content is below this, good delayed fracture resistance and corrosion resistance can be stably obtained.
[0054] The high-strength steel sheet of the present invention may be one in which the above-mentioned Zn-Co alloy layer is coated on one side of the substrate steel sheet, or one in which the Zn-Co alloy layer is coated on both sides of the substrate steel sheet.
[0055] The amount of the Zn-Co alloy layer can be calculated by dissolving the Zn-Co alloy layer on the substrate steel sheet and calculating the difference in mass between the steel sheet before and after dissolution. When the Zn-Co alloy layer is coated on only one side of the substrate steel sheet, the above mass difference (g) is divided by the area of one side of the substrate steel sheet (the above mass difference (g) / area of one side of the substrate steel sheet (m 2 )) can measure the coating amount of the Zn—Co alloy layer.
[0056] In addition, if the Zn-Co alloy layer is coated on both sides of the substrate steel sheet, the above mass difference (g) should be divided by twice the area of one side of the substrate steel sheet (the above mass difference (g) / (area of one side of the substrate steel sheet (m 2 )×2)), the coating amount of the Zn—Co alloy layer can be measured.
[0057] Furthermore, if the Co concentration in the Zn-Co alloy layer is less than 5 mass%, corrosion products with sufficient protective properties are not formed during the corrosion process, and hydrogen penetration into the steel sheet cannot be suppressed. Furthermore, if the Co concentration is 60 mass% or more, the delayed fracture resistance deteriorates. While the reason for this is unclear, it is thought that the corrosion resistance of the Zn-Co alloy deteriorates due to the influence of changes in the coating structure. Therefore, the Co concentration in the Zn-Co alloy layer is 5 mass% or more and less than 60 mass%, and preferably 10 mass% or more and less than 30 mass%, at which point the delayed fracture resistance is particularly good.
[0058] The Co concentration can be measured by ICP atomic emission spectroscopy using a solution obtained by dissolving the Zn-Co alloy layer. When the amount of Zn-Co alloy layer coating is small and calculation from the difference in mass of the steel sheet before and after dissolution results in a large error, more accurate coating amount and Co concentration can be obtained by measuring both Zn and Co in the Zn-Co alloy layer by ICP atomic emission spectroscopy.
[0059] There are no particular limitations on the method for coating the surface of the base steel sheet with a Zn-Co alloy layer, and any known method can be applied, such as electroplating (Zn-Co alloy electroplating) or vapor deposition.
[0060] In the case of electroplating (Zn-Co alloy electroplating), the Co concentration in the Zn-Co alloy layer can be changed by adjusting the concentrations of Zn and Co in the plating bath, and the coating amount of the Zn-Co alloy layer can be changed by adjusting the electrolysis time.In the case of vapor deposition, the Co concentration can be adjusted by using Zn and Co as targets, and the coating amount of the Zn-Co alloy layer can be changed by adjusting the vapor deposition time.
[0061] As described above, the high-strength steel sheet of the present invention may be one in which the above-mentioned Zn-Co alloy layer is coated on one side of the substrate steel sheet, or on both sides of the substrate steel sheet.
[0062] The Zn-Co alloy layer is basically made of Zn and Co, but may contain a small amount (total of 5 mass % or less) of one or more elements selected from Al, Fe, Ni, Mo, V, and W.
[0063] X-ray diffraction indicates that the Co in the Zn-Co alloy layer is not oxidized but is in an alloyed state. Because it is not in an oxidized state, it is presumed that it reacts during corrosion to form dense corrosion products.
[0064] The method for producing the base steel sheet used as the substrate is not particularly limited. To facilitate understanding of the present invention, a series of processes from steelmaking in the case where the surface of a cold-rolled steel sheet is coated with a Zn-Co alloy layer will be briefly described using an example.
[0065] Steel with a predetermined chemical composition is melted and continuously cast into a slab according to conventional methods. The resulting slab is then heated in a heating furnace at 1100-1300°C, hot-rolled at a finishing temperature of 750-950°C, and coiled at 500-650°C. This is followed by pickling and cold rolling at a reduction of 30-70%. If necessary, cleaning treatments are performed according to conventional methods, such as washing with an alkali or a mixed solution of alkali, surfactant, and chelating agent, electrolytic cleaning, hot water washing, and drying. The steel sheet is then heat-treated at 750-900°C and rapidly cooled to adjust the tensile strength. If necessary, temper rolling is performed according to conventional methods with an elongation rate of approximately 0.01-0.5%, thereby obtaining a cold-rolled steel sheet with the desired tensile strength. A Zn-Co alloy layer is applied to the surface of the cold-rolled steel sheet obtained in this manner by electroplating, vapor deposition, or other methods, to a coating amount of 0.10 g / m. 2 The Zn-Co alloy layer is coated in such a manner that the Co concentration is 5 mass % or more and less than 60 mass %, thereby obtaining a high-strength cold-rolled steel sheet as an example of the high-strength steel sheet of the present invention.
[0066] When a plating method, particularly an electroplating method, is used to coat the surface of a cold-rolled steel sheet with a Zn-Co alloy layer, and there is a risk of hydrogen penetrating into the steel sheet and the Zn-Co alloy layer during the plating process, the steel sheet may be held at a temperature of about 100 to 300°C for about 24 hours after the plating process, as necessary, to remove hydrogen that has penetrated into the steel sheet and the Zn-Co alloy layer.
[0067] The high strength steel sheet of the present invention has excellent delayed fracture resistance and excellent corrosion resistance, and can therefore be suitably used for automobile body or suspension parts.
[0068] The high strength steel sheet of the present invention can be suitably used in particular for side sills, lower center pillars and bumpers, which require excellent delayed fracture resistance and excellent corrosion resistance.
[0069] Furthermore, the high strength steel sheet of the present invention has excellent delayed fracture resistance and corrosion resistance, and is therefore useful for use in the lower arm portion of an automobile chassis.
[0070] In the present invention, delayed fracture resistance was evaluated using the test specimen shown in Figure 1 and a corrosion test specified in SAE J2334 shown in Figure 2. Details of the test specimen and the corrosion test will be described in the Examples. [Example]
[0071] The test specimens used as the substrate steel sheets were cold-rolled steel sheets (tensile strength 1480 MPa) with a thickness of 1.2 mm and containing each of the component compositions A to G in Table 1. These cold-rolled steel sheets were immersed in toluene and ultrasonically cleaned for 5 minutes to remove the rust-preventive oil, and then electroplated with a Zn-Co alloy to form a Zn-Co alloy layer (plated layer) on both surfaces of the steel sheets.
[0072] The above tensile strength was measured in accordance with JIS Z 2241 (2011).
[0073] [Table 1]
[0074] The electroplating solution used was one containing 30 g / L of divalent cobalt ions and 30 g / L of divalent zinc ions as sulfates, and 15 g / L of sodium acetate. The current density was 10 to 80 A / dm 2 The Co concentration in the Zn-Co alloy layer was changed by adjusting the range, and the coating amount of the Zn-Co alloy layer was changed by adjusting the electrolysis time, and steel sheets Nos. 1 to 23 and 25 to 48 were produced.
[0075] A steel sheet (No. 24) that was not subjected to the above plating treatment was used as one of the comparative examples.
[0076] The coating weight of the Zn-Co alloy layer was determined by immersing the steel sheet in hydrochloric acid to dissolve the Zn-Co alloy layer and measuring the difference in mass between the steel sheet before and after dissolution. The end point of the dissolution of the Zn-Co alloy layer was determined by adding an inhibitor to the hydrochloric acid to prevent iron from dissolving. By adding the inhibitor to the hydrochloric acid, gas was generated while the Zn-Co alloy layer was dissolving, but gas generation ceased once the dissolution of the Zn-Co alloy layer was complete. The completion of the dissolution of the Zn-Co alloy layer was determined by visually observing the end of this gas generation.
[0077] The Co concentration in the Zn-Co alloy layer was measured by ICP emission spectroscopy of a solution obtained by dissolving the alloy layer in hydrochloric acid.
[0078] The test pieces obtained as described above were subjected to the following evaluations. The results are shown in Table 2 together with the structure of the Zn—Co alloy layer.
[0079] (1) Evaluation of delayed fracture resistance A test specimen (30 mm × 99.5 mm) prepared by grinding was bent 180° with a radius of curvature of 4 mmR. As shown in Figure 1, this bent test specimen 1 was restrained with bolts 2 and nuts 3 so that the inner spacing was 8 mm, thereby fixing the specimen shape. A test specimen for delayed fracture evaluation was then subjected to a maximum of 80 cycles of cyclic corrosion testing, as specified in SAE J2334 (Society of Automotive Engineers of America) (Figure 2). The cycle consisted of one cycle (24 hours) consisting of the following steps: Step 1: Saltwater immersion (15 minutes in a solution containing 0.5% NaCl, 0.1% CaCl, and 0.075% NaHCO at 25°C); Step 2: Drying (17 hours and 45 minutes at 60°C and 50% RH); and Step 3: Wetting (6 hours at 50°C and 100% RH). This cycle was performed on weekdays (Monday through Friday). On non-weekdays (Saturdays and Sundays), only drying (24 hours in an environment of 60°C and 50% RH) was performed and was not included in the number of cycles performed. Before the salt water immersion process, which was the first process of each cycle, the steel sheets were visually inspected for the occurrence of cracks and the number of cycles to crack occurrence was measured. This test was also performed on three specimens of each steel plate, and the evaluation was based on the average value. Evaluation was based on the number of cycles and on the following criteria. A test in which the number of cycles to crack occurrence was 30 or more was deemed to have passed (○ or ◎). ◎: 40 cycles or more ○: 30 or more cycles, less than 40 cycles △: 10 or more cycles, less than 30 cycles ×: Less than 10 cycles
[0080] (2) Evaluation of corrosion resistance The samples that were subjected to the delayed fracture resistance evaluation were visually inspected for the presence or absence of red rust before each salt water immersion cycle, and the number of cycles until red rust occurred was counted. Evaluation was based on the number of cycles and on the following criteria. A sample with no red rust after five cycles was rated as passing (◯). ○: No red rust after 5 cycles ×: Red rust occurs in less than 5 cycles
[0081] [Table 2]
[0082] According to Table 2, all of the steel sheets of the present invention examples have excellent delayed fracture resistance and corrosion resistance. 2 More than 90g / m 2 It was found that steel plates Nos. 10, 12, 17, 18, and 25 to 48, in which the Co concentration in the Zn—Co alloy layer was 10 mass % or more and less than 30 mass %, had excellent corrosion resistance and very good delayed fracture resistance.
[0083] In contrast, the steel sheets of the comparative examples are inferior in either or both of delayed fracture resistance and corrosion resistance. [Explanation of symbols]
[0084] 1 test piece 2 bolts 3 nuts
Claims
1. A high-strength steel plate having a substrate steel plate having a tensile strength of 1180 MPa or more and a Zn-Co alloy layer coated on a surface of the substrate steel plate, the Zn-Co alloy layer having a coating weight per side of 20 g / m 2 or more and 50 g / m 2 or less, and the Zn-Co alloy layer having a Co concentration of 10 mass % or more and less than 30 mass %.
2. 2. The high-strength steel plate according to claim 1, characterized in that the base steel plate has a chemical composition containing, in mass%, C: 0.03% or more and 0.45% or less, Si: 0.01% or more and 3.00% or less, Mn: 0.5% or more and 3.5% or less, P: 0.050% or less, S: 0.0050% or less, Al: 0.001% or more and 1.500% or less, and N: 0.0100% or less, with the balance being Fe and unavoidable impurities.
3. The high-strength steel plate according to claim 2, characterized in that the base steel plate further contains, in mass%, one or more selected from Cu: 1.00% or less, B: 0.0050% or less, Nb: 0.100% or less, Ti: 0.200% or less, V: 0.500% or less, Mo: 1.000% or less, Cr: 1.000% or less, Ni: 1.00% or less, W: 0.200% or less, Zr: 0.200% or less, Hf: 0.200% or less, Co: 0.500% or less, Ca: 0.0050% or less, Mg: 0.0100% or less, Sn: 0.200% or less, Sb: 0.200% or less, and REM: 0.005% or less.
4. 4. An automobile body or suspension part using the high strength steel plate according to claim 1.
5. 4. An automobile body using the high strength steel sheet according to claim 1 in at least one of a side sill, a lower part of a center pillar, and a bumper.
6. 4. An automobile chassis using the high strength steel plate according to claim 1 in a lower arm portion.
Citation Information
Patent Citations
Surface treated steel sheet having high corrosion resistance
JP1985211096A
Production of zinc-cobalt plated steel material having high corrosion resistance
JP1993179481A
High strength galvanized steel sheet excellent in ductility and delayed fracture resistance and its production
JP1994145893A
High strength steel sheet with excellent resistance to hydrogen embrittlement, and its manufacturing method
JP2004231992A
High strength steel sheet excellent in delayed fracture resistance and corrosion resistance
JP2016186097A
